ESTIMASI BIOMASSA PERMUKAAN DAN STOK KARBON PADA TEGAKAN POHON Avicennia marina DAN Rhizophora mucronata DI PERAIRAN PESISIR OEBELO KABUPATEN KUPANG - Manafe, Glucklich; Kaho, Michael Riwu; Risamasu, Fonny (Bumi Lestari, 2016)
Mangrove forest has an important function for living thing especially in the ocean and coastal area. Besides as feeding and nursery ground, mangrove forest is also has a function as carbon sinker. The utilizing of mangrove forest as a corbon sinker is one of ways to reduce CO2 in atmosphere. Mangrove forest in Oebelo village has a capability to utilize as carbon sinker. The aim of this research was to estimate above ground biomass and carbon reserve from two mangrove species Avicennia marina and Rhizopora mucronata in coastal area of Oebelo Village. In this research data was collected from diameter breast high and litter from forest floor. Alometric was used to estimate the above ground biomass. After data collected, analysis would continue with t test to know the different between these two species.The result showed A. marina and R. mucronata were different, the highest biomass, carbon reserve and CO2 sequestration were in A.marina respectively 118.80 Mg.ha-1, 54.65 Mg.ha-1, 200.37 Mg.ha-1 and R. mucronata respectively 28.90 Mg.ha-1, 13.30 Mg.ha-1, 48.75 Mg.ha-1. The result for litter biomass and carbon reserve showed there was no different between these tow species.